Neglected obstetric haemorrhage leading to acute kidney injury - Verma, Pallavi; Dogra, Pavitra Manu; Sinha, Shivendra Kumar; Kaushik, Ramesh; Bhardwaj, Davinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pregnancy related acute kidney injury takes substantial share of acute kidney injury (AKI) in India, with obstetrical haemorrhage having high morbidity and mortality. A young female had neglected obstetric haemorrhage (unrecognized intrauterine and massive intraperitoneal bleeding post caesarean, due to uterine trauma and atony) and dangerous intra-abdominal hypertension with exsanguination eventually leading to shock, multifactorial AKI, metabolic acidosis, and hyperkalemia. Intensive and aggressive management with subtotal hysterectomy, inotropes, fluid management, mechanical ventilation, tracheostomy, and hemodialysis changed the outcome. Despite odds against, neglected obstetric haemorrhage with complicated AKI, was managed successfully by emergency hysterectomy, aggressive intervention for AKI with intensive fluid, ventilatory management and daily hemodialysis. Timely identification and aggressive management of this condition and complications is pivotal in preventing complications, morbidity, and maternal mortality.